(untitled) (Archives of Pediatrics of Uruguay, 2023)
This is the case of a newborn with cervical hemangioma and a subsequent diagnosis of subglottic hemangioma. Hemangiomas in neonates and infants require careful attention. Due to their growth pattern and the potential appearance of new lesions, they are considered unpredictable at this stage. A strong link was found between diffuse cervical-facial and symptomatic upper airway hemangiomas. The risk is related to the extent of skin involvement in a given area, which might include the jaw, chin, lower lip, and front of the neck skin. Infant hemangiomas require treatment when they present life-threatening and functional alterations, such as airway compromise.